2005
DOI: 10.1111/j.1365-2141.2005.05816.x
|View full text |Cite
|
Sign up to set email alerts
|

High expression of calcium‐binding proteins, S100A10, S100A11 and CALM2 in anaplastic large cell lymphoma

Abstract: SummaryAnaplastic large cell lymphomas (ALCL) are characterised by the presence of CD30-positive large cells, which usually are of T-cell type. Based on the presence or absence of translocations involving the anaplastic lymphoma kinase (ALK) locus, ALCL cases can be divided into two groups. To gain more insight in the biology of ALCL, we applied serial analysis of gene expression (SAGE) on the Karpas299 cell line and identified 25 up-and 19 downregulated genes. Comparison of the differentially expressed genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 53 publications
(56 reference statements)
1
21
0
Order By: Relevance
“…Former studies of gene expression in ALCL were restricted by the low number of transcripts analysed or by the use of cell lines or whole tissue sections. 21,[25][26][27][28][29][30] In the latter case, contamination by nonneoplastic cells can be significant (up to and partly 460% in the study of Lamant et al), which partly explains why the gene signatures associated to the ALK status in ALCL do not considerably overlap in our and Lamant's studies (not shown). 20 Although there will certainly be also some cellular contamination in our microdissected samples (approximately o10% as cells were selected as single cells or small groups of neoplastic cells), the similar phenotype of microdissected ALCL cells and ALCL cell lines in several important aspects like the relatedness to T, NK, resting or activated cells and NFkB target gene expression (not shown) argues against a major influence of our results by contaminating cells, as does the absence of expression of B-cell-specific genes (Supplementary Figure S2) or typical macrophage and dendritic cell genes (not shown) in the profiles of primary lymphomas.…”
Section: Discussionsupporting
confidence: 46%
“…Former studies of gene expression in ALCL were restricted by the low number of transcripts analysed or by the use of cell lines or whole tissue sections. 21,[25][26][27][28][29][30] In the latter case, contamination by nonneoplastic cells can be significant (up to and partly 460% in the study of Lamant et al), which partly explains why the gene signatures associated to the ALK status in ALCL do not considerably overlap in our and Lamant's studies (not shown). 20 Although there will certainly be also some cellular contamination in our microdissected samples (approximately o10% as cells were selected as single cells or small groups of neoplastic cells), the similar phenotype of microdissected ALCL cells and ALCL cell lines in several important aspects like the relatedness to T, NK, resting or activated cells and NFkB target gene expression (not shown) argues against a major influence of our results by contaminating cells, as does the absence of expression of B-cell-specific genes (Supplementary Figure S2) or typical macrophage and dendritic cell genes (not shown) in the profiles of primary lymphomas.…”
Section: Discussionsupporting
confidence: 46%
“…29 The alarmin family includes cytosolic calcium-binding proteins of the S100 family, HSPs, and HMGB proteins. It is becoming increasingly clear that the S100A8/A9 and HSP90 proteins, which are found in ALK ϩ ALCL cells, 6,7 are involved in many aspects of tumor growth and metastasis. 16,29 Although human primary lymphomas often overexpress HMGB-1 compared with normal samples, 11 until now, the role of HMGB-1 in ALK ϩ ALCL development and extranodal spreading had not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…4 ALK ϩ ALCL patients also present with an inflammatory syndrome characterized by high fever, lymphadenopathy or neutrophilia, release of various circulating inflammatory chemokines such as IL-8, 5 and expression of skin-inflammatory biomarkers such as the alarmins heat-shock protein 90 (HSP90), HSP70, 6 S100A8, or A11. 7 Recent studies have highlighted a role for IL-8 in mediating cutaneous skin inflammation and human keratinocyte hyperplasia associated with acanthosis (thickening of the skin). 8 IL-8 secreted by hyperplasic keratinocytes increases T-lymphocyte migration into the skin across both the vascular endothelium and the subendothelial matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SPs regulate many cellular processes such as cell growth, cell cycle progression, differentiation, transcription and secretion (15). Overexpression of several SPs has been reported in different stages and types of human tumors, such as anaplastic large cell lymphoma (16), uterine smooth muscle tumors (17), breast cancer (18), thyroid adenomas and carcinomas (19), invasive squamous cell carcinoma of the uterine cervix, serous adenocarcinoma of the ovary and invasive breast carcinoma (20). The overexpression of SPs in tumors suggests their potential role in tumorigenesis (21).…”
Section: Discussionmentioning
confidence: 99%